APORTACIONES DE A. AGUSTÍN Y G. FAERNO (MSS. 7901-2 BN) A LA ENMIENDA DE LOS FRAGMENTOS DE L. POMPINIO - Miralles Maldonado, José Carlos (Myrtia, 1993)
The author of this article analyzes the metrical and critical emendations written by the humanists A. Agustín (1517-1586) and G. Faerno (1510-1561) to the text of L. Pomponius’ ’Atellanae’. These unpublished notes, which may be found in the mss. 7901-2 from the BN of Madrid (’Fragmenta veterum latinorum scriptorum’), constitute the first attempt to put in order the extant fragments of the earlier latin poets. Unfortunately, this project remained unfinished, probably due to the publication of H. Estiènne’s ’Fragmenta’ (1564). In spite of the lack of a historical methodology, their research for the best and more appropriate ’lectiones’, according to the general sense and the metrical structure of each fragment, leads our humanists to propose accurate conjectures still surviving in modern editions, though ascribed to later scholars. In other cases, their comments, which are no more than approximations and provisional answers, can help us to correct or, at least, to find out some errors in the textual tradition.